2019
DOI: 10.3390/ijms20092198
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Colon Cancer-Associated Mutations in ADAM17: Modifications in the Pro-Domain Interfere with Trafficking and Maturation

Abstract: Colorectal cancer is one of the most commonly diagnosed malignancies in the Western world and is associated with elevated expression and activity of epidermal growth factor receptors (EGF-R). The metalloproteinase ADAM17 is involved in EGF-R activation by processing EGF-R ligands from membrane-bound pro-ligands. Underlining the link between colon cancer and ADAM17, genetic intestinal cancer models in ADAM17-deficient mice show a reduced tumor burden. In this study, we characterize point mutations within the AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Although there is evidence for CYB5 showing preferences for certain cytochrome P450 isozymes as well as particular reactions, we are not aware of any studies that included CYP2C8 57 . Interestingly, we found that HepaRG cells are homozygous for CYP2C8*3 , a relatively common variant reported to show altered interaction properties with POR and CYB5 in vitro 58 , 59 .…”
Section: Discussionmentioning
confidence: 85%
“…Although there is evidence for CYB5 showing preferences for certain cytochrome P450 isozymes as well as particular reactions, we are not aware of any studies that included CYP2C8 57 . Interestingly, we found that HepaRG cells are homozygous for CYP2C8*3 , a relatively common variant reported to show altered interaction properties with POR and CYB5 in vitro 58 , 59 .…”
Section: Discussionmentioning
confidence: 85%
“…This prevents the enzyme from cleaving proteins in an unspecific manner before reaching the Golgi, where its removal occurs by action of a pro-protein furin convertase [ 48 ]. The importance of the pro-domain in the regulation of ADAM17 is demonstrated in vivo by a cancer-associated point mutation that falls within its sequence (R177C) [ 49 ]. A further analysis in vitro shows that this mutation impaired ADAM17 proteolytic activity and its tracking to the cell membrane in a similar manner as a lack of the entire pro-domain affected its maturation [ 49 ].…”
Section: Adam17 Regulationmentioning
confidence: 99%
“…ADAM17 (ADAM metallopeptidase domain 17) is a membrane protein that contains 824 amino acids and its gene is located on chromosome 2. ADAM17 is widely expressed in various tissues including brain, heart, kidney, and skeletal muscle and its expression changes during embryonic development and life in adulthood (13). ADAM17 protein can regulate cellular signaling and affect cellular behavior, but the outcome always depends on the cell substrate.…”
Section: Introductionmentioning
confidence: 99%